Development and Validation of Interactive Teaching Materials Based on Universal Design for Learning for Digital Marketing Learning at the Open University - Kadarisman Kadarisman; Romi Siswanto; Rhini Patmasari; Sucipto Sucipto; Fitra Jaya (LP. Ma'arif Janggan Magetan, 2025)
The research aimed to develop and validate an interactive learning module effectively applicable in distance education. Using an Educational Research and Development (R&D) model with a mixed-methods approach, the study collected quantitative and qualitative data. Quantitative data were obtained from pre-tests and post-tests to measure cognitive improvement, analyzed using descriptive and inferential statistics (paired t-test or Wilcoxon test) and effect size calculation. Learning analytics from the LMS—such as clicks, video-watching duration, and quiz scores—supported the analysis. Qualitative data were gathered through semi-structured interviews, participant observation, and thematic analysis by Braun and Clarke, complemented with Likert-scale questionnaires, observation rubrics, and LMS logs. The findings revealed a significant improvement in students’ cognitive performance, with post-test scores (M = 13.24, SD = 1.07) much higher than pre-test scores (M = 3.67, SD = 1.41), t(19) = 25.43, p < 0.001, Cohen’s d = 5.69. LMS analytics showed high engagement, with 82% average video completion and frequent quiz participation. Over 85% of students reported greater satisfaction and motivation using the interactive module. The integration of short videos, diagnostic quizzes, and web simulations proved effective for self-directed learning and comprehension, supporting the Universal Design for Learning (UDL) framework in inclusive digital education.